Estimation of Stature from Inter-Acromial Length in Western Indian Population: A Pilot Study - Anam, Ekta; Patel, Manasi; Phatak, Ajay; Kumar, Lavlesh; Agarwal , Swapnil Sudhirkumar (Journal of Indian Academy of Forensic Medicine, 2014)
Stature estimation is a standard practice in the fields of Bio-Archaeology, Forensic, Biological and  Palaeoanthropology. It can be accomplished most accurately by anatomical reconstruction, followed by  type I regression equations using long bones of the lower limb. The skeletal remains presented to the  Forensic departments are often incomplete and thus Forensic experts have to rely on other elements. As no existing equations are clearly appropriate, this study aims to formulate a regression  equation to establish relationship between stature and inter-acromial length of living  individuals.Measurements were taken from 100 randomly selected medical students between 22-29 years  of age, native to Gujarat, India, using spreading calliper (least count 1 mm). The documented  measurement data was analyzed using SPSS software version 11.Three sets of regression equations  were derived which revealed that predictive value from the equations was unsatisfactory.The study  concluded that inter-acromial length is not a good parameter for stature estimation. Further detailed  studies are recommended to support or negate the finding.
Keywords: Inter-Acromial Length; Stature; Correlation; Regression Equation